Ikoniczność w tekstach epistolarnych Michaiła Bułhakowa - Rycielska, Beata (Studia Rossica Posnaniensia, 2017)
The article pertains, in broad terms, to the concept of imaging of an act in language proposed by Ronald W. Langacker within the framework of cognitive grammar. In the narrow sense, it depicts one of the parameters of imaging — diagrammatical quantitative iconicity. The iconicity was described by applying the theory of a network model. On the basis of letters written by Mikhail Bulgakov, it was possible to distinguish concepts which result from the quantity of the linguistic form creating an utterance and which appear in context. They supplement an open list of meanings of the quantitative iconicity category that have been previously defined by researchers.